ANALISIS FRAMING BERITA KORUPSI MASSAL PROYEK PEMBANGUNAN RUANG TERBUKA HIJAU (RTH) TUNJUK AJAR INTEGRITAS PEKANBARU DI SURAT KABAR RIAU POS DAN TRIBUN PEKANBARU - Sintia Devi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the interest of writer to mass corruption case of development project Ruang Terbuka Hijau (RTH) Tunjuk Ajar Integritas Pekanbaru. This is because first, the involvement of 18 suspects in this corruption case. Secondly, in the Ruang Terbuka Hijau (RTH) Tunjuk Ajar Integritas Pekanbaru there is an Integrity Monument inaugurated by the Chairman of the Komisi Pemberantasan Korupsi (KPK) Agus Raharjo on December 10, 2016. It coincides with the commemoration of International Anti-Corruption Day in Indonesia which is centered in Riau. Thirdly, followed by Dwi Agus Sumarno who is the son-in-law of Annas Maamun, former governor of Riau. This study aims to determine the framing structure of news and ideology of Riau Pos and Tribun Pekanbaru in packing the news.This qualitative research uses framing analysis of Zhondang Pan and Gerald M. Kosicki as well as media political economy theory. Data collection was done with news documentation, interviews with both parties of the media concerned, and observation by analyzing the news.The first result of research, framework structure of Riau Pos syntax tend to be closed in representation. Scripts, Riau Pos apply accommodative journalism in accordance with the rules of journalism 5W + 1H. Thematic, showing neutrality and providing cover both side through the suspect. Rhetorical, diction used more nuanced activity. While the structure of syntactic framing Tribun Pekanbaru, the content displayed more daring. Tribun less attention to accommodative journalism in accordance with the rules of journalism 5W + 1H. The favor of the government is clearly apparent in the Thematic element. While on the elements of Rhetoric, Tribun is rich with images and graphics. The results of the second study, have an ideological equation from the point of view of media political economy theory. Holistic, these two media view the economic approach because this news has a relationship with social, economic, political and cultural factors around the media, especially the people of Pekanbaru. Historically, the analysis of political economy attributes the position of these two media by modifying the news of mass corruption of development project Ruang Terbuka Hijau (RTH) Tunjuk Ajar Integritas Pekanbaru as a commercial product of the company. The study of political economy, the two media did not deny the high value of news of the event but they further uphold the principle of editorial policy embedded in their ideology. Riau Pos by maintaining the image of the government as well as the country, although impressed hidden in the representation and Tribun Pekanbaru by stimulating the reader to be active and reactive to this event with a wealth of graphics and layout.Keywords: Mass Corruption, Ruang Terbuka Hijau (RTH) Tunjuk Ajar Integritas Pekanbaru, Framing Analysis, Riau Pos, Tribun Pekanbaru.